Optimal channel allocation algorithm with efficient channel reservation for cellular networks. (19th February 2008) - Krishna, P. Venkata; Iyengar, N.Ch.S.N.
Today, there is a rapid growth of mobile users. As the available frequency spectrum is limited, it must be efficiently utilised. This paper proposes a dynamic channel allocation scheme with efficient channel reservation for handoff calls. The proposed algorithm deals with both originating calls and handoff calls. In the proposed algorithm, we reserve some channels for handoff calls. Later, it increments or decrements, the reserved channels dynamically based on the traffic. Quality of Service (QoS) may be improved further by reserving the channels for handoff calls based on the user mobility and type of cell. The reservation factor, which varies the number of reserved channels, is based on both the blocking probability and the dropping probability. The results indicate clearly that the proposed channel allocation scheme exhibits better performance by considering the above said user mobility and type of cells. Also, it reduces the call dropping rate than the existing channel allocation schemes.